Analysis of Economic Land Value (Land Rent) on Agricultural Land in Deli Serdang Regency - Permata, Eka Tresna; Nasution, Zulkifli; Purwoko, Agus (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Deli Serdang Regency is a district that in its development is experiencing quite rapid development. Changes in agricultural land use from 2009 - 2019 in Deli Serdang Regency are quite significant. The purpose of this study was to analyze changes in the use of agricultural land between 2009 - 2019, analyzing the economic value of the land and factors that affect the economic value of agricultural land in Deli Serdang Regency. The analysis is based on Geographic Information System (GIS), land economic analysis, and multiple linear regression analysis.